2021
DOI: 10.1038/s41598-021-85341-z
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field and TGF-β enhance the compensatory plasticity after sensory nerve injury in cockroach Periplaneta americana

Abstract: Recovery of function after sensory nerves injury involves compensatory plasticity, which can be observed in invertebrates. The aim of the study was the evaluation of compensatory plasticity in the cockroach (Periplaneta americana) nervous system after the sensory nerve injury and assessment of the effect of electromagnetic field exposure (EMF, 50 Hz, 7 mT) and TGF-β on this process. The bioelectrical activities of nerves (pre-and post-synaptic parts of the sensory path) were recorded under wind stimulation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Both peripheral ( Eccles et al, 1963 ; Jankowska et al, 2021 ) and central ( Carpenter et al, 1963 ; Andersen et al, 1964 ; Fetz, 1968 ) mechanisms have been shown to contribute to regulate Ia sensory transmission. GABAergic neurons contributing to regulate Ia sensory transmission receive innervation from the brain and spinal cord ( Rudomin and Schmidt, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both peripheral ( Eccles et al, 1963 ; Jankowska et al, 2021 ) and central ( Carpenter et al, 1963 ; Andersen et al, 1964 ; Fetz, 1968 ) mechanisms have been shown to contribute to regulate Ia sensory transmission. GABAergic neurons contributing to regulate Ia sensory transmission receive innervation from the brain and spinal cord ( Rudomin and Schmidt, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both peripheral 35,36 and central 37-39 mechanisms have been shown to contribute to regulate Ia sensory transmission. GABAergic neurons contributing to regulate Ia sensory transmission receive innervation from the brain and spinal cord 13 .…”
Section: Discussionmentioning
confidence: 99%